Water Management for field crops production - Chandra (Journal of Agricultural Extension Management, 2025)
Efficient water management requires multidisciplinary approach and calls for working together, by users, the farmers, agronomists and irrigation engineers. The water management technology is highly location specific and as such the management decision vary with quantity, quality and time of water availability, topography, soil characteristics, climatic conditions, crops to be grown, sowing time and other agronomic practices